Minimal Anthropology and Testimony. Józef Tischner's Philosophy of Education - Miłosz Hołda (Nicolaus Copernicus University in Toruń, 2018)
The article contains a new interpretation of Józef Tischner's philosophy of education. It consists of two elements: 'minimal anthropology' and testimony. Tischner's 'minimal anthropology' contains criticisms of erroneous anthropological trends and an indication of the values that must be taken into account in order to build an adequate anthropology. The role of the testimony is to show how these values can be realized. Tischner not only proposed the philosophy of education, but also was a philosopher-educator. His Christian-inspired philosophy of education and the testimony of life can be a valuable inspiration for all those who reflect in this area.